2009
DOI: 10.1155/2009/378245
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Induced Asthma Symptoms and Nighttime Asthma: Are They Similar to AHR?

Abstract: Background. Asthma experienced during exercise and during the night is based on the presence of airway hyperresponsiveness (AHR). The aim of the present study was to examine whether AHR is a predictor of exercise-induced asthma (EIA) and nighttime symptoms. Material. We included 793 asthmatics subjects with symptoms and a positive asthma test. Results. Mean (SD) FEV1 was 93% (15), 71% had rhinitis, and 62% had atopy. Both EIA and nighttime symptoms were associated with AHR; however, when including other facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Treatment with Beta 2 agonist, salbutamol is considered to be a first choice for treatment young athletes with EIB, inhaled Beta 2 agonists are first line medication of EIB both as treatment and prophylaxis of EIB, because of its rapid onset of action a short acting beta 2 agonists should be taken 15 min pre-exercise [3,22] the most common therapeutic recommendation to decrease or inhibit symptoms of EIB is the prophylactic use of short acting bronchodilators (beta 2 agonists) such as Salbutamol (Ventolin inhaler) shortly preexercise, these agent work by simulating Beta 2 -receptors on the bronchial smooth muscle causing muscle fibers relaxation and bronchodilation as well as possibly inhibit mast cell degranulation. SABAs given by mouth inhalation 5-20 min pre-exercise are usually effective for 2-4 hours in protecting against or attenuating EIB [16,19,20,22] . Pervious study showed that SABA are most effective drugs to reduce EIB providing complete protection against EIB (90%) of subject when given immediately before exercise, this results agreed with thin study the protection is 88.2% of EIB in female patients [30] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with Beta 2 agonist, salbutamol is considered to be a first choice for treatment young athletes with EIB, inhaled Beta 2 agonists are first line medication of EIB both as treatment and prophylaxis of EIB, because of its rapid onset of action a short acting beta 2 agonists should be taken 15 min pre-exercise [3,22] the most common therapeutic recommendation to decrease or inhibit symptoms of EIB is the prophylactic use of short acting bronchodilators (beta 2 agonists) such as Salbutamol (Ventolin inhaler) shortly preexercise, these agent work by simulating Beta 2 -receptors on the bronchial smooth muscle causing muscle fibers relaxation and bronchodilation as well as possibly inhibit mast cell degranulation. SABAs given by mouth inhalation 5-20 min pre-exercise are usually effective for 2-4 hours in protecting against or attenuating EIB [16,19,20,22] . Pervious study showed that SABA are most effective drugs to reduce EIB providing complete protection against EIB (90%) of subject when given immediately before exercise, this results agreed with thin study the protection is 88.2% of EIB in female patients [30] .…”
Section: Discussionmentioning
confidence: 99%
“…SABA inhibits Bronchospasm by stimulating β 2 receptors on mast cell so prevent the release of contractile mediators and inducing relaxation of the airway smooth muscle fibers. This drug is taken as 2 puffs 15 minutes before exercise and lasts 4 to 6 hours, these agents like salbutamol and terbutaline [6,10,15,16] . The goals of this study are to determine the incidence rate of EIB among the girl intermediate school students and to manage this occult type of asthma, also to enable patients to exercise at all intensity level without serious respiratory limitation.…”
Section: Pathophysiologymentioning
confidence: 99%